Development and evaluation of an automated spray patternator using digital liquid level sensors - Luck, J. D.; Schaardt, W. A.; Forney, S. H.; Sharda, Ajay (My University, 2016)
The purpose of this study was to develop and evaluate an automated spray pattern measurement system which utilized digital liquid level sensors to quantify the coefficient of variation (CV) for different nozzle configurations. The overall system was designed to measure nozzle effluent in 25 mm divisions from 38.1 to 76.2 cm in width for multiple nozzle configurations with a total patternator surface width of 3.05 m. The patternator surface and data collection system were designed and developed to achieve three primary goals: patternator surface division accuracy, data collection system accuracy, and data collection system repeatability. Patternator surface measurements indicated an average standard deviation of approximately 0.1 mm (0.4%) which would not contribute significantly to spray pattern CV estimates. To quantify the measurement accuracy, the automated system was compared to manual data collection using weights collected from graduated cylinders. Statistical analysis revealed no difference (p > 0.05) between CV estimates from the manual and automated data collection methods. The average difference in CV between the two methods was 0.15% which considered 12 tests per method. Repeatability was also a primary concern, the standard deviation among CV values for tests conducted with the automated system was only 0.35%. The evaluation of the system provided confidence that suitable results would be acquired for different nozzle configurations consisting of acceptable or relatively poor spray patterns. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Luck, J. D., Schaardt, W. A., Forney, S. H., & Sharda, A. (2016). Development and evaluation of an automated spray patternator using digital liquid level sensors. Applied Engineering in Agriculture, 32(1), 47-52. doi:10.13031/aea.32.11381
Keywords: Pesticides; Spray Boom; Sprayers; Spraying Equipment